Melville Weston Fuller papers - Fuller, Melville Weston, 1833-1910.
Correspondence, speeches and writings, notes, scrapbooks, printed matter, and memorabilia relating to Fuller's term on the Supreme Court; his law practice, real estate holdings, and Democratic politics in Chicago, Ill.; his work as a member of the Permanent Court of Arbitration especially in relation to the matter of the Muscat dhows and the Venezuelan boundary dispute; Fuller's personal and family affairs; and his childhood in Maine and student life at Bowdoin College, Brunswick, Maine.
Family correspondents include Henry Weld Fuller, Mary Ellen Coolbaugh Fuller, Joseph Emerson Smith, Catherine Weston Fuller Wadleigh, Nathan Weston, Paulina B. Weston, and other members of the Fuller, Weston, and Coolbaugh families.
Other correspondents include Richard Everard Webster, Viscount Alverstone; Hugh L. Bond; William H. Brawley; David J. Brewer; Charles Henry Butler; Joseph Hodges Choate; Grover Cleveland; J.C. Bancroft Davis; William R. Day; John W. Doane; A.H. Garland; Stephen Strong Gregory; Walter Quintin Gresham; Benjamin Harrison; John Hay; Farrer Herschell, Baron Herschell; Henry M. Hoyt; Philander C. Knox; Heinrich Lammasch; Daniel Scott Lamont; Robert Todd Lincoln; Fedor Fedorovich Martens; William McKinley; William H. Moody; Henry C. Morris; John Morris; Richard Olney; Baron Julian Pauncefote; Erskine Mason Phelps; William L. Putnam; Theodore Roosevelt; Elihu Root; Henry M. Shepard; Charles H. Simonton; William M. Springer; Henry Stone; Oscar S. Straus; William H. Taft; Lambert Tree; Hugh Campbell Wallace; William A. Wheeler; and George W. Wickersham.
Library of Congress Prints and Photographs Division.
Lawyer and jurist; chief justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alverstone, Richard Everard Webster, -- Viscount, -- 1842-1915 -- Correspondence; Bond, Hugh L. -- 1828-1893 -- Correspondence; Brawley, William H., -- 1841-1916 -- Correspondence; Brewer, David J. -- 1837-1910 -- Correspondence; Butler, Charles Henry, -- 1859-1940 -- Correspondence; Choate, Joseph Hodges, -- 1832-1917 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Davis, J. C. Bancroft -- 1822-1907 -- Correspondence; Day, William R. -- 1849-1923 -- Correspondence; Doane, John W. -- Correspondence; Fuller, Henry Weld, -- 1810-1889 -- Correspondence; Fuller, Mary Ellen Coolbaugh, -- 1837-1904 -- Correspondence; Garland, A. H. -- 1832-1899 -- Correspondence; Gregory, Stephen Strong, -- 1849-1920 -- Correspondence; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Herschell, Farrer Herschell, -- Baron, -- 1837-1899 -- Correspondence; Hoyt, Henry M. -- 1830-1892 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Lammasch, Heinrich, -- 1853-1920 -- Correspondence; Lamont, Daniel Scott, -- 1851-1905 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Martens, Fedor Fedorovich, -- 1845-1909 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Moody, William H. -- 1853-1917 -- Correspondence; Morris, Henry C. -- 1868- -- Correspondence; Morris, John -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Pauncefote, Julian, -- Baron, -- 1828-1902 -- Correspondence; Phelps, Erskine Mason, -- 1839-1910 -- Correspondence; Putnam, William L. -- 1835-1918 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Shepard, Henry M. -- Correspondence; Simonton, Charles H. -- 1829-1904 -- Correspondence; Smith, Joseph Emerson, -- 1835-1881 -- Correspondence; Springer, William M. -- Correspondence; Stone, Henry, -- 1830-1896 -- Correspondence; Straus, Oscar S. -- 1850-1926 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tree, Lambert, -- 1832-1910 -- Correspondence; Wadleigh, Catherine Weston Fuller -- Correspondence; Wallace, Hugh Campbell, -- 1863-1931 -- Correspondence; Wheeler, William A. -- 1833-1874 -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Coolbaugh family -- Correspondence; Fuller family -- Correspondence; Weston family -- Correspondence; United States. -- Supreme Court; Bowdoin College -- Students; Democratic Party (Ill.); Permanent Court of Arbitration; Constitutional law -- United States; Law -- United States; Real estate investment -- Illinois -- Chicago; Practice of law -- Illinois -- Chicago; Shipping -- Oman -- Muscat; Universities and colleges -- Maine -- Brunswick; Chicago (Ill.) -- Politics and government